Graph matching based on spectral embedding with missing value - Tang, Jin; Jiang, Bo; Zheng, Aihua; Luo, Bin (Pattern recognition, 2012)
This paper proposes an efficient algorithm for inexact graph matching based on spectral embedding with missing value. We commence by building an association graph model based on initial matching algorithm. Then, by dot product representation of graph with missing value, a new embedding method (co-embedding), where the correspondences between unmatched nodes are treated as missing data in an association graph, is presented. At last, a new graph matching algorithm which alternates between the co-embedding and point pattern matching is proposed. Convictive experimental results on both synthetic and real-world data demonstrate the effectiveness of the proposed graph matching algorithm. ► Inexact graph matching based on spectral embedding with missing value. ► Co-embedding with missing data in association graph. ► Experimental results show the effectiveness of our method.